DOI: 10.11606/t.88.2012.tde-22102012-112635
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da corrosão e corrosão-fadiga em ligas de Al e Al - Li de alta resistência para aplicação aeronáutica

Abstract: estarem sempre ao meu lado nos momentos felizes e de dor. Sei que são meus amigos de verdade, pois, sempre suportaram minha felicidade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
8

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
1
3
0
8
Order By: Relevance
“…Comparing both alloys when tested in a saline fog environment, it is observed that the AA2128-T851 presented a slight improved corrosion fatigue resistance. This fact may be linked to the corrosion results obtained by Moreto 24 . This author has concluded that the AA2128-T851 exhibited a better corrosion resistance than AA2524-T3, therefore it is more resistance to oxidation in the presence of the saline fog during the corrosion fatigue tests, that the testing time was much shorter than the 15 days of the salt spray tests.…”
Section: Resultssupporting
confidence: 53%
“…Comparing both alloys when tested in a saline fog environment, it is observed that the AA2128-T851 presented a slight improved corrosion fatigue resistance. This fact may be linked to the corrosion results obtained by Moreto 24 . This author has concluded that the AA2128-T851 exhibited a better corrosion resistance than AA2524-T3, therefore it is more resistance to oxidation in the presence of the saline fog during the corrosion fatigue tests, that the testing time was much shorter than the 15 days of the salt spray tests.…”
Section: Resultssupporting
confidence: 53%
“…This kind of knowledge is only developed by research and for that reason request a series of tests and provides the necessary material for the laboratory of mechanical tests of EESC-USP. This was how were developed works as the Moreto (2012) or Pascoal (2014) and the present research continued going deeper in the same direction in order to supply new tools for designers. The aspects of fatigue structure design touched in the present work are highlighted, in Figure 1.…”
Section: Statement Of the Problemmentioning
confidence: 84%
“…The A1 test was done by others researchers (Pascoal, 2014) and (Moreto, 2012) and the tests A2, A3, A4, and C1 were done by the present author in addition of some of the mentioned researchers in order to add results to validate them.…”
Section: Tests Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme já mencionado, a primeira constante de tempo a altas frequências (AF) é relacionada com o óxido passivo (R ox /C ox ) na superfície das ligas e da junta soldada; a segunda, a médias frequências (MF) é associada com processos de transferência de carga e o carregamento da dupla camada elétrica (R ct /CPE dl ) e a terceira, a baixas frequências (BF), a processos de corrosão na liga exposta ao meio corrosivo, nas regiões de defeito do filme óxido. A escolha do CEE em cascata foi feita a partir de modelos já propostos na literatura para a liga 2XXX e 7XXX (QUEIROZ, 2002;MORETO, 2012). dois MB e para a junta soldada obtidas a partir do PCA após 2 horas de imersão em solução 10 mM de NaCl.…”
Section: Circuito Elétrico Equivalente (Cee)unclassified